Intestinal parasitic infections among children aged 7–14 years in Mizan-Aman city, Southwest Ethiopia: a community-based cross-sectional study - Tekalign, Eyob; Sebeta, Asresash; Nureye, Dejen; Duguma, Tadesse; Tesfaye, Tarkegn (Frontiers in Public Health, 2024)
BackgroundIntestinal parasitic infections continue to pose a major threat to human health globally, with a particularly high prevalence in developing countries. Soil-borne helminthiasis and schistosomiasis are notably widespread.ObjectiveThe objective of the study was to determine the prevalence and contributing factors of intestinal parasites infection among participants aged 7–14 years.MethodsCommunity-wide prevalence study was undertaken from 30 August to 30 September 2021 in Mizan Aman Town. Socio-demographic information was collected using questionnaires. Three of the five kebels were randomly chosen. Households with children aged 7–14 were gathered from the chosen kebels and health post to recruit one eligible subject. Allocation of study subjects to each of the chosen kebels was computed proportionally. Two thick smear of Kato Katz technique was applied to examine stool samples. Data were entered and analyzed using SPSS version 20. To investigate the association between the dependent and independent variables, a logistic regression analysis was conducted. Statistics were considered significant for p-values under 0.05.ResultsThe overall prevalence of intestinal parasites was 64.6% (215/333). Of these, 51.05% (170/333) were infected with STHs, while 13.5% (45/333) had S. mansoni. T. trichiura was the most prevalent helminth. Infection intensity ranged from light to moderate was observed. Prior information about STHs (aORr:2.022 = CI:1.222–3.340), poor knowledge about STHs (aOR:1.677 = CI:1.057–2.660), unaware of deworming as prevention method of S. mansoni (aOR:2.620:CI:1267–5.418), swimming (aOR:0.448:CI:0.176–0.992) and contact with water (aOR:0.402:CI:0.169–0.957) were significantly associated with the S. mansoni infection.Conclusion and recommendationThe prevalence of intestinal parasite was high. Heavy infection was not recorded. Beyond mass deworming, the report emphasizes the necessity of ongoing public health interventions to address the high prevalence of these intestinal helminths.